THE IMPACT OF CURRICULUM AND INSTRUCTION MODEL TOWARDS RELIGIOSITY, SPIRITUALITY, AND BEHAVIOR OF ADOLESCENTS - dkk, Herlina (Prodi Teknologi Pendidikan, 2015)
Abstract, The present research aims at testing the impact of curriculum and instruction model towards religiosity and behavior of adolescent. Participants for the research are 634 high school students with gender percentage as following: 58% female students and 42% male students. The participants are students from Daarut Tauhid high school (SMA Daarut Tauhid) and PGII high school (SMA PGII) as representative of schools employing Islamic-based curriculum (IC), and SMA Kartika Siliwangi, SMA Negeri 23 and SMA Negeri 24 as representative of schools employing national curriculum (NC). The result of the research shows a significant difference between schools with IC and schools with NC in terms of students’ religiosity. In addition, significant difference is also found between schools with IC and schools with NC in terms of students’ spirituality. Moreover, the behavioral observation of students of schools with IC and students of schools with NC results on finding of significant difference as well. Integration of two factors—Islamic-based curriculum and boarding school model—would result on an effective and powerful aspect to develop students’ religiosity and spirituality, as well as reducing deviant and risky behavior. However, without the integration, Islamic-based curriculum itself is not a major factor in reducing deviant behavior in high school students; therefore, other potential factors should be integrated with the curriculum in playing important roles to develop students’ religiosity and spirituality and reducing deviant behavior. Keywords: Islamic-based curriculum, religiosity, spirituality, deviant or risky behavior. Abstrak,Penelitian ini bermaksud untuk menguji dampak kurikulum dan model pembelajaran terhadap religiusitas dan perilaku remaja. Sampel penelitian ini berjumlah 634 partisipan dengan proporsi jenis kelamin 58% perempuan dan 42% laki-laki yang merupakan siswa SMA Daarut Tauhid dan SMA PGII yang dianggap mewakili sekolah dengan kurikulum bermuatan Islam, dan SMA Kartika Siliwangi, SMA Negeri 23, dan SMA Negeri 24 yang dianggap mewakili sekolah dengan kurikulum nasional. Hasil penelitian menunjukkan bahwa terdapat perbedaan yang signifikan antara religiusitas siswa sekolah dengan kurikulum bermuatan agama dan siswa sekolah berkurikulum nasional. Selain itu penelitian ini menunjukkan bahwa terdapat perbedaan yang signifikan antara spiritualitas siswa sekolah dengan kurikulum bermuatan agama dan siswa sekolah berkurikulum nasional. Hasil yang sama juga terjadi ketika menguji signifikansi perbedaan antara perilaku siswa di sekolah dengan kurikulum bermuatan agama dan siswa sekolah berkurikulum nasional. Kurikulum berbasis Islam dan model sekolah boarding school adalah dua faktor yang secara bersama-sama yang paling kuat meningkatkan religiusitas, spiritualitas, dan menurunkan perilaku menyimpang atau beresiko. Sedangkan kurikulum berbasis Islam bukan faktor utama atau ada faktor lain yang bisa menurunkan perilaku menyimpang siswa SMA.Kata kunci: Kurikulum, religiusitas, spiritualitas, perilaku yang menyimpang atau beresiko melanggar aturan, remaja